Professional Identity in Analysis: A Systematic Review of the Literature - Cardoso, Maria Inês Silva Teixeira (2014)
The present study is a systematic review of literature, with the objective to map the typology of conceptual studies about professional identity, as well as the used conceptual fields and the evidence therefrom resulting. The research was made within the electronic databases ISI web of Knowledge, EBSCO (Academic Search Complete, ERIC and Sport Discus) and B-On, between 2002 and 2011. The research equation was "Professional Identity" AND "Review", in the fields ‘abstract’, ‘topic’ and ‘title’ having been integrated 22 articles. The content analysis was the technique used, with the following categories defined a priori: i) typology studies; (ii) conceptual framework around the professional identity; iii) indications for future researches about teacher's identity. The results showed a marked increase of publications in 2011, in large professional areas (teachers and nurses) and in two main stages of development (the learning and professional process), as well as a strong conceptual positioning of authors in the perspective of symbolic interactionism and in post-modernity. It was also clear that the concept of professional identity fits simultaneously in individual (personal and social) and collective dimensions. Indeed, it involves the individual, his/her relationship with the other in a given context and his/her sense of belonging to a group. Regarding the proposals for future investigations, the researches with a qualitative nature (ethnographic and longitudinal) in work places prevails, with emphasis on the observation of dynamics established in communities of practice and its speeches (public and private), in a combination of micro and macro analysis.